A Cell Model Suitable for a High-Throughput Screening of Inhibitors of the Wnt/β-Catenin Pathway - Grimaldi, Marina; Boulahtouf, Abdelhay; Prévostel, Corinne; Thierry, Alain; Balaguer, Patrick; Blache, Philippe (Frontiers in Pharmacology, 2018)
A constitutive activation of the Wnt/β-catenin pathway is an initiating event in colon carcinogenesis. We developed colon cancer cells models that highlight the non-selectivity of previously described inhibitors of the Wnt pathway and we propose our model as a suitable screening system for inhibitors of the pathway.